Normative Acts of the Ruler in Ancient Near Eastern Law - Fijałkowska, Lena (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The article presents a survey of legislative acts issued by ancient Near Eastern rulers. The ancient oriental civilizations being devoid of any legal doctrine, no classification of those acts was ever compiled. The king was not bound by any formal requirements regarding a particular form of legislation and could choose to include norms of civil or criminal law in otherwise purely administrative acts, or, conversely, add administrative regulations to collections of civil and penal rules.